A court of mist and fury - Maas, Sarah J. (New York : Bloomsbury, 2017)
Feyre survived Amarantha's clutches to return to the Spring Court--but at a steep cost. Though she now has the powers of the High Fae, her heart remains human, and it can't forget the terrible deeds she performed to save Tamlin's people. Nor has Feyre forgotten her bargain with Rhysand, High Lord of the feared Night Court. As Feyre navigates its dark web of politics, passion, and dazzling power, a greater evil looms--and she might be key to stopping it. But only if she can harness her harrowing gifts, heal her fractured soul, and decide how she wishes to shape her future--and the future of a world torn apart. From back cover.
Includes an excerpt from A court of wings and ruin.
Sequel to: A court of thorns and roses.
Keywords: Tam Lin (Legendary character) -- Adaptations -- Juvenile fiction; Magic -- Juvenile fiction; Fairies -- Juvenile fiction; Courts and courtiers -- Juvenile fiction; Fantasy; Fairies -- Fiction; Courts and courtiers; Fairies; Magic; Tam Lin (Legendary character); Juvenile works; Fiction; Fantasy fiction; Fantasy fiction; Fiction; Juvenile works; Fantasy fiction